PENGARUH PENAMBAHAN PERSENTASE BERAT FIBER E-GLASSTERHADAP PENYERAPAN AIR PADA BAHAN FIBER REINFORCED COMPOSITE - , NYAYU WULAN TRI UTAMI, Dr.drg.Siti Sunarintyas,M.Kes ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Fiber reinforced composite (FRC) is a combination of material between the polymer matrix and fiber. There is great interest in development of FRC in dentistry because support the concept of minimally invasive. Fiber reinforced composite (FRC) are used inte oral cavity causing the material will interact with saliva which is mostly water constituent. This study aimed to determine the effect of adding weight percentage of E-glass fiber towards water absorption in FRC. Samples in this research used flowable matrix composite (Master Flow BIODINAMICA, Brazil) dan E-glass fibers (R338-2400/V/P, Stick Tech Ltd., Turku, Finland). The sample size used were 2mm x 2mmx 25mm which were activated by visible light source (blue-LED , litex 695tm, Dentamerica, USA) for 20 seconds. There were three groups, they were resin composite without fiber (3 samples), FRC with E-glass fiber 38% (3 samples), and FRC with E-glass fiber 76% (3 samples). Samples were stored in distilled water (10 ml) for 7 days with a temperature of 370C. Water absorption was measured in percentage (%). Measurement of samples weight used electronic digital weighing scales 0,1mg accuracy. The result were analyzed statistically with One Way ANOVA, continued by Post Hoc Test using Least Significant Different (LSD). The result showed the average water absorption of the group resin composite without fiber, FRC with E-glass fiber 38% and FRC with E-glass fiber 76% were 0.885 ± 0.07 %, 0.462 ± 0.06 % and 0.435 ± 0.15 %, respectively. The conclusion of this study was there was significant effect between adding weight percentage of E-glass fiber to water absorption in FRC (p<0,05).